Insect pollination of cycads - Toon, Alicia; Terry, L. Irene; Tang, William; Walter, Gimme H.; Cook, Lyn G. (Austral ecology, 2020)
Most cycads have intimate associations with their insect pollinators that parallel those of well‐known flowering plants, such as sexually deceptive orchids and the male wasps and bees they deceive. Despite this, the mistaken belief that cycads are mostly wind‐pollinated is still commonly expressed. Perhaps as a consequence, cycad–pollinator systems are rarely exemplified in studies of the role of pollinators in plant evolution and diversification. Although first recognised more than a century ago, specialised associations between cycads and their insect pollinators have been elucidated experimentally only in the past few decades. This review covers the history of understanding pollination in cycads, the advances that have been made since the 1980s using field observations and experiments, and analyses of molecular data from the population to phylum level. We outline areas for future research to address how such interactions might have affected speciation and extinctions. We stress that inclusion of cycads in broader considerations of the role of pollinators in plant diversification is important because they are phylogenetically distant from flowering plants and their pollination systems might have evolved independently of one another. This review is timely because cycads are a globally threatened group that might be vulnerable to co‐extinction with pollinator loss.